History of Church Music: A General Overview - Hutabarat, Franklin (Jurnal Koinonia: Fakultas Filsafat Universitas Advent Indonesia, 2023)
The development of Church liturgical music today cannot be separated from the development of Church music over time. It is commonly understood that attempting to describe the over 2000-year history of the Church's music in a single tract is impractical. As a result, the breakdown is broad, allowing us to see the progression of Church music from one epoch to the next. Church music is influenced or exists in the context of history as a whole, as well as the context of music history as a whole. This paper focuses on the systematic review and examination of published primary sources that are kept in various collections, libraries, and record centers. The bibliography digs deeper into these sources as well as archival collections. The history of liturgical music has its unique musical style in every era. There is Baroque music (17th century), Renaissance music (15-17th century), Classical music (18th century), Romantic music (19th century), Impressionist music (late 19th century) but faded after World War I, and various modern music of the 20th century, both profane (such as jazz, tango, pop, rock, and so on) and religious. Today, music is regarded as an integral aspect of the Church's liturgy. Keywords: Church, Church Music, Liturgy, Music History